2002
DOI: 10.4049/jimmunol.168.11.5415
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of HLA Class I Molecules on Endothelial Cells Induces Phosphorylation of Src, Paxillin, and Focal Adhesion Kinase in an Actin-Dependent Manner

Abstract: The development of chronic rejection is the major limitation to long-term allograft survival. HLA class I Ags have been implicated to play a role in this process because ligation of class I molecules by anti-HLA Abs stimulates smooth muscle cell and endothelial cell proliferation. In this study, we show that ligation of HLA class I molecules on the surface of human aortic endothelial cells stimulates phosphorylation of Src, focal adhesion kinase, and paxillin. Signaling through class I stimulated Src phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
119
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 64 publications
11
119
0
Order By: Relevance
“…[11][12][13][14] Here, patients with DSA anti-HLA antibodies against class II molecules had elevated levels of EndMT markers, and the PTC expressed fascin de novo in an experimental model of ABMR. These findings confirm that these DSAs are harmful for endothelial cells that survive immunologic injury.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…[11][12][13][14] Here, patients with DSA anti-HLA antibodies against class II molecules had elevated levels of EndMT markers, and the PTC expressed fascin de novo in an experimental model of ABMR. These findings confirm that these DSAs are harmful for endothelial cells that survive immunologic injury.…”
Section: Discussionmentioning
confidence: 85%
“…In vitro and in vivo experiments, [11][12][13][14] as well as human data from kidney recipients, 4 concur to show that the binding of DSA to endothelial cells profoundly affects the endothelial transcriptome. Molecules involved in inflammation, coagulation, cell motility, and endothelial repair are synthesized, with phenotypic changes reminiscent of an endothelial-tomesenchymal transition (EndMT).…”
mentioning
confidence: 74%
“…In vitro anti-MHC class I antibodies promote endothelial proliferation via increased expression of basic FGF receptors, increased phosphorylation of Src, and NF-B levels (60). Anticlass I antibodies increase endothelial resistance to apoptosis, as manifested by increased Bcl-xL, Bcl-2, and HO-1, and increased activity of phosphatidylinositol-3-kinase and Akt pathways and resistance to complement-mediated lysis (50,51).…”
Section: Antibody and Complement Effects On Endotheliummentioning
confidence: 99%
“…However, molecular mechanisms and signaling pathways implicated in HLA class I-mediated EC proliferation remain unclear. Allospecific Ab-mediated ligation of class I molecules expressed on the surface of EC have been shown to trigger intracellular signaling events reflected by phosphorylation of Src, paxillin, and focal adhesion kinase (8). Activation of the PI3-K/Akt pathway also occurs in response to class I ligation on EC (21).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it has been shown that anti-HLA Ab, developed by transplant recipients after transplantation, are capable of transducing signals via HLA class I molecules, which stimulate cell proliferation (6). Furthermore, ligation of class I molecules with Ab also results in increased tyrosine phosphorylation of several intracellular proteins on EC (7,8). Treatment of cells with IFN-␥ and TNF-␣ upregulated MHC class I expression and potentiated anti-HLA Abmediated proliferative responses (9).…”
mentioning
confidence: 99%